The costs of maritime supply chain disruptions : the case of the Suez Canal blockage by the ‘Ever Given’ megaship - Tran, Nguyen Khoi; Haralambides, Hercules; Notteboom, Theo; Cullinane, Kevin (International Journal of Production Economics, 2025)
In March 2021, the six-day blockage of the Suez Canal, caused by the grounding of Evergreen's 'Ever Given' containership, created chaos in global trade. The 400-m giant lodged horizontally in a 265-m wide stretch of the canal and the efforts to dislodge and refloat it were unprecedented, involving dredging, towing and lightering. The accident marked one of the most severe disruptions at a key chokepoint in the international shipping network. Using ship voyage data, this research introduces a model to quantify the economic losses of a carrier's containership fleet, caused by such a disruption. The studied impacts include ship costs, environmental costs, and inventory-carrying costs. The model is applied to Maersk Line's East-West network, with 69 vessels (0.84m TEUs) affected by the blockage, either by having to reroute via the Cape of Good Hope or by the delays caused during and after the blockage. The results point to an additional 44,574 tonnes of CO2 produced by the extended trips and extra waiting times of the Maersk ships. The total losses incurred amount to $88.79m, comprising ship costs of $8.04m, environmental costs of $4.46m and, most strikingly of all, inventory-carrying costs of $76.29m, stemming from the high value of goods onboard ($26.5bn). Ship deviations also resulted in revenue losses for the Suez Canal Authority (SCA) of $5.86m, from Maersk crossings alone. Additionally, the research findings shed light on the vulnerabilities of maritime supply chains, particularly concerning prolonged roundtrips, changes to port call patterns, and extended cargo delivery times.